Molecular aspects of pancreatic β‐cell dysfunction: Oxidative stress, microRNA, and long noncoding RNA. Issue 6 (22nd November 2018) - Saeedi Borujeni, Mohammad Javad; Esfandiary, Ebrahim; Baradaran, Azar; Valiani, Ali; Ghanadian, Mustafa; Codoñer‐Franch, Pilar; Basirat, Reyhane; Alonso‐Iglesias, Eulalia; Mirzaei, Hamed; Yazdani, Amid
Abstract: Metabolic syndrome is known as a frequent precursor of type 2 diabetes mellitus (T2D). This disease could affect 8% of the people worldwide. Given that pancreatic β‐cell dysfunction and loss have central roles in the initiation and progression of the disease, the understanding of cellular and molecular pathways associated with pancreatic β‐cell dysfunction can provide more information about the underlying pathways involved in T2D. Multiple lines evidence indicated that oxidative stress, microRNA, and long noncoding RNA play significant roles in various steps of diseases. Oxidative stress is one of the important factors involved in T2D pathogenesis. This could affect the function and survival of the β cell via activation or inhibition of several processes and targets, such as receptor‐signal transduction, enzyme activity, gene expression, ion channel transport, and apoptosis. Besides oxidative stress, microRNAs and noncoding RNAs have emerged as epigenetic regulators that could affect pancreatic β‐cell dysfunction. These molecules exert their effects via targeting a variety of cellular and molecular pathways involved in T2D pathogenesis. Here, we summarized the molecular aspects of pancreatic β‐cell dysfunction. Moreover, we highlighted the roles of oxidative stress, microRNAs, and noncoding RNAs in pancreatic β‐cell dysfunction.